Wikidata And Covid-19: Creating A Collaborative Knowledge Graph From Cord-19 Scholarly Publications - Turki, Houcemeddine (My University, 2020)
Knowledge graphs are an essential ingredient for information systems to handle the ever growing COVID-19 data on a daily basis. This presentation explains how open and collaborative FAIR knowledge bases like Wikidata can be useful to create a large-scale semantic representation of COVID-19 information from CORD-19 scholarly publications. I give an overview of how a data model has been collaboratively developed and maintained for COVID-19 knowledge, and I provide a detailed snapshot about the various methods used to extract items and statements from CORD-19 research papers. Then, I outline the tools for the enrichment of COVID-19 information on Wikidata as well as the knowledge graph validation methods applicable to COVID-19 knowledge. Finally, I describe the COVID-19 information in Wikidata and discuss its usefulness in supporting human decisions and social recommendations about the infectious disease.
Keywords: Public health surveillance; Wikidata; Knowledge graph construction